ANALISIS PERBANDINGAN TINGKAT PENGEMBALIAN SIMPANAN MUDARABAH DAN PENGEMBALIAN EKUITAS PADA BANK UMUM SYARIAH PERIODE 2014-2018 - Effendi, Bashid; Wahyudi, Sugeng (Faculty of Economics and Business Diponegoro University, 2019)
The objective of this research were 1) to compare the Return on MudarabahDeposits (ROMD) and the Return on Equity (ROE) in Islamic banking, and 2) to examinethe factors that affect ROMD and ROE. This research used quarterly data from 6 (six)Islamic banks over the period of 2014 – 2018 and was examined by multiple linearregression. Purposive sampling used as sampling method in this study.This research resulted several substantial findings. First, Return on MudharabahDeposits was lower than shareholder’s Return on Equity. Second, ROMD was positivelyinfluenced by Profit Attributable to Depositors as Percentage of Operating Profit(PADOP) and negatively influenced by Total Deposit as Percentage of Total Assets(TDTA), meanwhile Return on Assets (ROA) did not have an influence on ROMD. Third,ROE was positively influenced by ROA and negatively influenced by Total Equity asPercentage of Total Assets (TETA), while Profit Attributable To Equityholders asPercentage of Operating Profit (PAEOP) did not have an influence on ROMD on ROE.